(untitled) (Colombia Medica, 1981)
A review of clinical histories from 1955 to 1980 at the Hospital Universitario, Cali, Colombia, produced 18 benign submucosal tumors of the stomach. The most common was leiomy oma, with 14 cases, 5 of which were ulcerated. More cases were seen among men, and 11 cases occurred in patients up to 50 years old. These tumors may simulate peptic ulcers, gastric carcinoma, and diseases with high digestive hemorrhage. Their clinical features, as well as their radiological characteristics, are discussed